PENGARUH PENGGUNAAN APLIKASI CANVA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV DI SEKOLAH DASAR - Patmawati Koswara; Nurani Hadnistia Darmawan; Ragil Nurdiansyah; Rahma Ubaidillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low cognitive learning outcomes of students in the Natural and Social Sciences (IPAS) subject matter on Climate and Its Changes in class IV of SD Negeri Cibarehong. The gap between the characteristics of Alpha Generation students who tend to be visual and the limitations of conventional media is the main cause of the sub-optimal understanding of student concepts. This study aims to determine the students' initial ability (pretest) and final ability (posttest), as well as analyze the significant effect of using the Canva application as a learning medium on students' cognitive learning outcomes. The research method used is quantitative with a Pre-Experimental design in the form of One-Group Pretest-Posttest Design. The population in this study were all fourth-grade students of SD Negeri Cibarehong using Total Sampling technique to obtain a sample of 26 students. Data were collected using test instruments in the form of 15 multiple-choice questions and 5 essay questions that have been tested for validity and reliability. The data analysis technique used descriptive statistics and inferential tests through Paired Sample T-Test assisted by the SPSS 26 program. The results showed that the students' pretest average value of 55.46 (low category) increased significantly in the posttest average value to 84.08 (high category). The hypothesis test results showed that the value of tcount > ttable (52.358 > 2.060) and the significance value (Sig. 2-tailed) of 0.000 < 0.05, so that H0 was rejected and Ha was accepted. Based on the observation sheet, the implementation of the researcher's teaching activities using Canva media reached a percentage of 89.58% with Very Good criteria. Thus, it can be concluded that the use of the Canva application provides a very significant positive effect on increasing students' cognitive learning outcomes in IPAS subjects in elementary schools.